Abnormal Endothelial Gene Expression Associated With Early Coronary Atherosclerosis. Issue 14 (21st July 2020) - Hebbel, Robert P.; Wei, Peng; Milbauer, Liming; Corban, Michel T.; Solovey, Anna; Kiley, James; Pattee, Jack; Lerman, Lilach O.; Pan, Wei; Lerman, Amir
Abstract : Background: We examined feasibility of a unique approach towards gaining insight into heritable risk for early atherosclerosis: surveying gene expression by endothelial cells from living subjects. Methods and Results: Subjects aged <50 years (mean age, 37; range, 22–49) without obstructive coronary artery disease underwent coronary reactivity testing that identified them as having normal or abnormal coronary endothelial function. Cultures of Blood Outgrowth Endothelial Cells (BOEC) from 6 normal and 13 abnormal subjects passed rigorous quality control and were used for microarray assessment of gene expression. Of 9 genes differentially expressed at false discovery rate <0.1%, we here focus upon abnormal subjects having elevated expression of HMGB1 (high mobility group box 1) which we unexpectedly found to be linked to low LAMC1 (laminin gamma 1) expression. This linkage was corroborated by 3 of our past studies and confirmed bio‐functionally. Compared with normal BOEC, abnormal BOEC released 13±3‐fold more HMGB1 in response to lipopolysaccharide; and they deposited one tenth as much LAMC1 into collagen subendothelial matrix during culture. Clinical follow‐up data are provided for 4 normal subjects (followed 13.4±0.1 year) and for 12 abnormal subjects (followed 9.1±4.5 years). Conclusions: The known pathogenic effects of high‐ HMGB1 and low‐ LAMC1 predict that the combination would biologically converge upon the focal adhesion complex, to the detriment of endothelial shear responsiveness. This gene expression pattern may comprise a heritable risk state that promotes early coronary atherosclerosis. If so, the testing could be applied even in childhood, enabling early intervention. This approach offers a way to bridge the information gap between genetics and clinical phenotype.